(untitled) (Journal of Intellectual Property Rights (JIPR), 2024)
Inventive step is the sine qua non for the grant of a patent. Arguably, this subjective evaluation of the claimed invention ensures a sufficient leap forward to the existing technology. The footnote appended to Article 27 of the TRIPS Agreement contemplates that inventive step may be deemed tobe synonymous with“non-obvious”. Thus, the footnote has left it openended for the WTO members to speculate on may or may not situations or entirely rule out this apparent inventive step/nonobviousness equivalence suggestion. TRIPS Agreement does not define inventive step or lay down the standards to be followed in construing the person from whose perspective the claimed invention has to be looked into for inventive step/non-obviousness determination. In the U.S., Congress and the Courts have consistently interpreted “non-obviousness” as technical advancement to the concerned discipline. When it comes to Indian law, there is an apparentclarity, but when delved deep, the outcome lacks crucial elements of predictability. Section 2(1)(ja) of the Indian Patents Act, 1970 is framed in such a way so that it gives an impression to the reader that technical advancement and being non-obvious to a person skilled in the art are two distinct concepts. The US Courts always gave economic considerations a secondary status in the determination of the non-obviousness of a given invention. Indian patent statute specifically mentions economic significanceand places it as an alternative to technical advancementwithoutclarifying the interconnection of the two connotations.The authors intend to understand, in what way technical advance can be considered as a completely separate standalone criterion for patentability in conjunction with non-obviousness. Furthermore, as a step forward, the authors want to expound on whether economic consideration alone,without even requiring non-obviousness, can fulfil the inventive step criterion in India.